Puzzle: At the Zoo (Tulsa, OK EDC Publishing, 2018)
A vibrantly illustrated 100-piece jigsaw showing a busy zoo, plus a 24-page picture puzzle book presented together in a colourful sturdy box. The jigsaw measures 59 x 40cm and both the jigsaw and puzzle book are packed with things to spot and talk about. Can you spot a tiger wearing pyjamas, three donkeys, the zookeeper's keys and lots more?